2013
DOI: 10.1037/a0030135
|View full text |Cite
|
Sign up to set email alerts
|

A social exchange-based model of the antecedents of workplace exclusion.

Abstract: We conducted 2 studies of coworker dyads to test a theoretical model exploring why and under what circumstances employees are the targets of workplace exclusion. Adopting a victim precipitation perspective, we integrate belongingness and social exchange theories to propose that employees who display workplace incivility are distrusted and therefore are targets of workplace exclusion. Highlighting the importance of the context of the perpetrator-target relationship, we also find support for the postulation that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(153 citation statements)
references
References 80 publications
7
144
0
2
Order By: Relevance
“…Deviant work behavior can result from employees who feel mistreated by others in the organization and could be a way to retaliate against other employees. For example, Scott [14] found that employees were more likely to engage in retaliatory acts because of disparaging remarks made against them.…”
Section: Explanation Of Counterproductive Work Behavior (Cwb)mentioning
confidence: 99%
“…Deviant work behavior can result from employees who feel mistreated by others in the organization and could be a way to retaliate against other employees. For example, Scott [14] found that employees were more likely to engage in retaliatory acts because of disparaging remarks made against them.…”
Section: Explanation Of Counterproductive Work Behavior (Cwb)mentioning
confidence: 99%
“…Although it may be beneficial in future work to differentiate the foci of co-op ostracism and examine if differential responses are prompted, our conceptualisation of the construct was driven by prevailing theoretical and empirical considerations. In this regard, the vast majority of available literatureparticularly the empirical one, such as workplace ostracism studies (Cullen et al, 2012;Leunga et al, 2011;O'Reilly et al, 2014;Scott et al, 2013;Wu et al, 2012) -suggests that ostracism or its responses are not dependent on the source. Besides, a mere one-person exclusion is sufficient to elicit negative outcomes, even against inclusive individuals who may be seen as part of the excluding alliance (Chernyak and Zayas, 2010;Critcher and Zayas, 2014).…”
Section: 80mentioning
confidence: 99%
“…Although some may think it is an extreme or infrequent event, people experience about one ostracism episode every day (Nezlek et al, 2015). Individuals are ostracised in interpersonal friendships and relationships (Poulsen and Carmon, 2015), by close others or strangers (Nezlek et al, 2012), by in-group or out-group members (G omez et al, 2011), online (Wolf et al, 2015), in workplaces (Scott et al, 2013;Wu et al, 2011) and in marketplaces (Mattila et al, 2013;Mead et al, 2011).…”
Section: Ejm 529/10mentioning
confidence: 99%
“…Both the social psychological and organizational literature suggest that age is related to the occurrence of workplace exclusion, thus, age is controlled for in this study. The paper also controlled for the tenure and education because of the possibility that employees newer who have had less time to develop meaningful work relationships may report levels of exclusion than those with more years of tenure [13] and one's level of education is associated with substance abuse [59] which often associated with acts of exclusion while at work. Finally, we controlled for the income because of Diener, Louis, and Shigehiro (2013) [60] found that rising household income is significantly associated with all three forms of subjective well-being.…”
Section: Control Variablementioning
confidence: 99%
“…Most researchers focus on the detrimental consequences of ostracism in the workplace [8], such as presenting challenges that can lessen the resources individuals hold [9] which cause employees experience emotional exhaustion [10] and deteriorated psychological well-beings [11]; associating with undesirable behaviors, examples as acting rudely, withholding assistance and mocking with others [12]; increasing individuals' job stress and turnover intention and decreasing job performance [9]. There is little concern about the factors that precipitate the occurrence of this phenomenon [13]. Just as Wu, Wei, and Hui (2011) [11] note that examinations of the antecedents of Workplace Ostracism is indeed significant, on account of only when the antecedents are designated, can efficacious measures be taken to minimize the occurrence of Workplace Ostracism.…”
Section: Introductionmentioning
confidence: 99%